For love of liberty [videorecording (DVD)] : the story of America's black patriots : [a film] - Berry, Halle; Martin, Frank (Television producer); Powell, Colin L.; Freeman, Morgan; Cosby, Bill, 1937-; Glover, Danny; Travolta, John, 1954- (Melee Entertainment Home Video : Vivendi Entertainment, 2009)
Gain an unprecedented look at the experiences and accomplishments of African Americans in the military, and learn why such a group of heroic men and women would fight for the freedom of others that they themselves weren't able to enjoy. Hosted by Halle Berry with an introduction by Colin Powell, and features the voices of Morgan Freeman, Bill Cosby, Danny Glover, John Travolta, and many more.